2017
DOI: 10.1016/j.bpj.2017.04.049
|View full text |Cite
|
Sign up to set email alerts
|

DNA Internal Motion Likely Accelerates Protein Target Search in a Packed Nucleoid

Abstract: Transcription factors must diffuse through densely packed and coiled DNA to find their binding sites. Using a coarse-grained model of DNA and lac repressor (LacI) in the Escherichia coli nucleoid, simulations were performed to examine how LacI diffuses in such a space. Despite the canonical picture of LacI diffusing rather freely, in reality the DNA is densely packed, is not rigid but highly mobile, and the dynamics of DNA dictates to a great extent the LacI motion. A possibly better picture of unbound LacI mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Entropic unmixing might therefore limit the ability of a newly acquired replicon to find a target sequence for integration. In good agreement with this hypothesis it appeared that DNA internal motion likely accelerates protein target search in a packed nucleoid (Chow & Skolnick, 2017) Material and methods…”
Section: Could Partition Of Genetic Materials Imposes Constrains On Gementioning
confidence: 70%
“…Entropic unmixing might therefore limit the ability of a newly acquired replicon to find a target sequence for integration. In good agreement with this hypothesis it appeared that DNA internal motion likely accelerates protein target search in a packed nucleoid (Chow & Skolnick, 2017) Material and methods…”
Section: Could Partition Of Genetic Materials Imposes Constrains On Gementioning
confidence: 70%
“…The nucleoid can become a barrier for larger, ribosome-sized, proteins or protein-aggregates that are too large to diffuse through the meshwork presented by the DNA (Figure 2E ) (Bakshi et al, 2012 ). In a model of LacI diffusion in the nucleoid it was concluded that DNA dynamics determines the motion of LacI to a large extent (Chow and Skolnick, 2017 ). During an osmotic upshift, next to the increased crowding, invaginations provide temporal barriers for proteins (Mika et al, 2010 ) until the cell recovers its volume and resumes growth.…”
Section: Overview Of Diffusion Rates and Their Consequences In Prokarmentioning
confidence: 99%
“…Binding of LacI can also be near specific (i.e., to sequences that are closely related to the cognate sequence, e.g., the lac operator in this case). To these interactions, one should also add the presence of chromosomal DNA motions within the nucleoid, which have been suggested to accelerate target search for DNA-binding proteins such as LacI [52] .…”
Section: Non-specific Interactionsmentioning
confidence: 99%